2015
DOI: 10.4103/2231-0762.151980
|View full text |Cite
|
Sign up to set email alerts
|

Premolar extraction in orthodontics: Does it have any effect on patient′s facial height?

Abstract: Objectives:Facial esthetics is an important part of the orthodontic treatment. Many cases frequently require premolar extraction, either for relief of crowding or for profile change. Supposedly, extraction provides some vertical reduction. This investigation challenges the clinical effects of such treatment protocols.Patients and Methods:This was a retrospective and quasi-experimental study. Records of 60 patients in their post-pubertal age were randomly selected for this study. The criteria for case selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…These findings are in concordance with the study conducted by Zafarmand and Zafarmand, where the bicuspid extraction theory (neither 2 nor 4 premolar extractions) for reducing the facial height did not provide any significant changes post-treatment. 36 The vertical angle and the lower anterior facial height increased in both of their groups. This was also highlighted in a study conducted by Staggers, according to whom the biomechanical justification for this could be the intrinsic extrusive effect of most orthodontic modalities, e.g., the protraction of posterior teeth, which can unfavorably compensate any reduction in the facial height.…”
Section: Discussionmentioning
confidence: 91%
“…These findings are in concordance with the study conducted by Zafarmand and Zafarmand, where the bicuspid extraction theory (neither 2 nor 4 premolar extractions) for reducing the facial height did not provide any significant changes post-treatment. 36 The vertical angle and the lower anterior facial height increased in both of their groups. This was also highlighted in a study conducted by Staggers, according to whom the biomechanical justification for this could be the intrinsic extrusive effect of most orthodontic modalities, e.g., the protraction of posterior teeth, which can unfavorably compensate any reduction in the facial height.…”
Section: Discussionmentioning
confidence: 91%
“…Several previous studies have shown that changes in relation between the size of the teeth and the length of the curve are multifactorial, depending on the overbite, the overjet, the inclination of the anterior teeth, the intercanine width, the intermolar width, the curve width, and the curve of Spee [9].…”
Section: Methodsmentioning
confidence: 99%
“…6,7,8 Cusinamo et al suggested that premolar extraction did not increase facial height. 9,10 Instead, research conducted by Wyatt proved that premolar retraction followed by anterior teeth retraction in orthodontic treatment of class II division 1 malocclusion might cause posterior displacement of the condyle and disc transfer into the anterior thus causing vertical dimension changes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above descriptions we are interested in researching the vertical dimension changes of lower anterior facial height and incisors in class II division 1 malocclusion orthodontic treatment with Edgewise technique by extraction of two maxillary premolars. 9,10…”
Section: Introductionmentioning
confidence: 99%